Islamic Approaches to Healing: Culturally Grounded Mental Health and Psychosocial Support in Post-Conflict Aceh and Beyond - Fatimah Zuhra; Raudhatul Jannah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2026)
Muslim-majority regions in Southeast Asia—Aceh, Mindanao, and Patani—continue to face mental health and psychosocial challenges despite reduced political violence. This systematic review examines how Islamic values are integrated into Mental Health and Psychosocial Support (MHPSS) programs in post-conflict settings. Using the PRISMA framework, 20 peer-reviewed and grey literature sources (2004–2025) were analyzed. Findings show that Islamic practices such as zikr and worship contribute to mental well-being and illness prevention, while psychospiritual interventions enhance emotional resilience and recovery. Religious leaders and institutions often exert greater influence than clinical professionals, reflecting strong community trust in faith-based support. However, implementation is limited by shortages of trained Islamic-oriented MHPSS providers, few specialized institutions, and persistent mental health stigma. This review proposes a culturally grounded MHPSS framework integrating Islamic values and highlights implications for policymakers, practitioners, and humanitarian actors supporting Muslim post-conflict communities.